Paleomagnetism and Tectonics of the South Shetland Islands and the Northern Antarctic Peninsula - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
New paleomagnetic data presented here from 61 sites in Paleozoic, Mesozoic and Cenozoic igneous and sedimentary rocks from the Antarctic Peninsula and the South Shetland Islands constrain the relative motion of the Antarctic Peninsula since the mid-Cretaceous and allow the quantification of tectonic rotation between the different blocks recognized within the area. Paleozoic and Jurassic results failed the fold test and suggest an important remagnetization in the area. The similarity between these results and those obtained from Cretaceous intrusives indicates a mid-Cretaceous age for the remagnetization. The paleopoles obtained for the different blocks and for different ages suggest that there is no relative rotation among them. These combined results allow us to obtain a Cretaceous (90 Ma) and Paleocene (60 Ma) paleopole. These paleopoles document a very low apparent polar wandering of the Antarctic Peninsula for the last 100 Ma. (c) 2010 Elsevier B.V. All rights reserved.